Humanitarian Innovation Project - Review, F (Refugee Studies Centre, University of Oxford, 2014)
The Humanitarian Innovation Project (HIP) www.oxhip.org is housed within the Refugee Studies Centre at the University of Oxford and focuses specifically on the refugee context.